2015
DOI: 10.12940/jfb.2015.19.2.69
|View full text |Cite
|
Sign up to set email alerts
|

Research on Intention to Adopt Smart Wear: Based on Extended UTAUT Model

Abstract: The objective of this study is to investigate the intention to adopt smart wear, based on extended UTAUT model. We examined the effects of performance expectancy (PE), effort expectancy (EE), hedonic motivation (HE), social influence (SI), facilitating conditions (FC), and price value (PV) on the intended adoption of smart watch and smart shoes, respectively. In addition, moderating effects of gender, age, and innovation resistance were examined. An online survey was conducted, comprised of 2030 consumers who … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 11 publications
1
1
0
Order By: Relevance
“…PV was found to elicit a significant impact on BI. The findings of Nair et al (2015), Sung and Sung (2015), and Xu (2014) agreed with the outcome of this research, and it can be concluded that the cost and charges of mobile learning affect the intention of students in applying mobile learning system. Learners are prone to embrace the technology when it harvests greater benefits compared to the cost (Isa & Wong, 2015).…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…PV was found to elicit a significant impact on BI. The findings of Nair et al (2015), Sung and Sung (2015), and Xu (2014) agreed with the outcome of this research, and it can be concluded that the cost and charges of mobile learning affect the intention of students in applying mobile learning system. Learners are prone to embrace the technology when it harvests greater benefits compared to the cost (Isa & Wong, 2015).…”
Section: Discussionsupporting
confidence: 85%
“…In contrast with the organisational use setting, individual consumers generally endure the monetary cost of using a technology (Yang, 2013). The findings of Nair, Ali, and Leong 2015, Sung and Sung (2015), and Xu 2014showed that BI is significantly influenced by PV. This leads to the next hypothesis:…”
Section: Price Valuementioning
confidence: 94%